Integrating rehabilitation, restoration and conservation for a sustainable jarrah forest future during climate disruption - Wardell-Johnson, Grant; Calver, M.; Burrows, N.; di Virgilio, Giovanni (C S I R O Publishing, 2015)
The environment of the northern jarrah (Eucalyptus marginata) forest (NJF) of Mediterranean-climate, south-western Australia is characterised by deeply weathered soil profiles and low fertility, reflecting long geological stasis. This fire-prone environment is characterised by primary forests of low productivity but high biomass. Since European settlement (1829), the NJF has been structurally transformed by deforestation and resource extraction, including logging and mining (principally for bauxite). Rainfall has declined by 15–20% since 1970, with projections for further decline. A new hydrological regime foreshadows regolith drying, with a changed climate leading to more unplanned, intense fires. Declining productivity, coupled with rehabilitation more suited to a wetter climate, places stress on tree growth and compromises biodiversity. Thus, ecological disruption likely follows from interactions between climate change and historical exploitation. The complex challenges posed by these interactions require multifaceted and novel solutions. We argue that under drying conditions, maintenance of productivity while conserving biodiversity can best be achieved by changing the focus of rehabilitation to the understorey. This would coincide with protecting and restoring surrounding unmined forest with emphasis on the overstorey.Presently, state-of-the-science rehabilitation seeks to restore jarrah forest, following bauxite mining. This goal is unlikely to be achievable across extensive areas under climate change projections. Rather, a focus on restoring understorey following mining would provide a more positive water balance in the wider forest matrix. This approach recognises loss of forest values through mining, but anticipates conservation of biodiversity and important elements of forest structure by minimising ecologically unacceptable disturbance to surrounding forest.